2001
DOI: 10.1046/j.1365-2605.2001.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric evaluation of the human prostate

Abstract: In order to clarify the ageing-related histological changes in the human prostate, a quantitative morphometric analysis was performed. Complete prostates were obtained at autopsy from 281 men (aged 20-84 years) who died in traffic accidents and presented no clinical symptoms of prostatic disease. The prostates were classified as: histologically normal (n=182), with nodular hyperplasia (n=42), with intraepithelial neoplasia (n=40) and carcinomatous with low Gleason grade (n=20). Each prostate was divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
36
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 12 publications
12
36
2
Order By: Relevance
“…The comparison of our results with data from the literature for young adult nonhyperplastic prostate glands (Bartsch et al 1979;Arenas et al 2001;Chagas et al 2002;Matsuda et al 2006) is shown in Table 4. Because in the study of Bartsch et al (1979) and Chagas et al (2002) mean percent volumes of prostate stroma and glandular epithelium only were measured, we calculated mean percent volumes of the glandular lumen (L) as the remainder "100−S(%)−E(%)" and the glandular component (GC = E + L) as the remainder "100−S (%)".…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…The comparison of our results with data from the literature for young adult nonhyperplastic prostate glands (Bartsch et al 1979;Arenas et al 2001;Chagas et al 2002;Matsuda et al 2006) is shown in Table 4. Because in the study of Bartsch et al (1979) and Chagas et al (2002) mean percent volumes of prostate stroma and glandular epithelium only were measured, we calculated mean percent volumes of the glandular lumen (L) as the remainder "100−S(%)−E(%)" and the glandular component (GC = E + L) as the remainder "100−S (%)".…”
Section: Resultssupporting
confidence: 56%
“…Also, that study provided evidence that the S/E ratio of the prostate remains constant in males from birth to age 40 years and equals 6:1. These findings did not agree with the morphometric studies of some other researches (Bartsch et al 1979;Arenas et al 2001;Chagas et al 2002;Matsuda et al 2006).…”
contrasting
confidence: 58%
See 3 more Smart Citations